Low pre-existing endemic human coronavirus (HCoV-NL63)-specific T cell frequencies are associated with impaired SARS-CoV-2-specific T cell responses in people living with HIV - Ng’uni, Tiza L.; Musale, Vernon; Nkosi, Thandeka; Mandolo, Jonathan; Mvula, Memory; Michelo, Clive; Karim, Farina; Moosa, Mohomed Yunus S.; Khan, Khadija; Jambo, Kondwani Charles; Hanekom, Willem; Sigal, Alex; et al. (Frontiers in Immunology, 2024)
Background: Understanding how HIV affects SARS-CoV-2 immunity is crucial for managing COVID-19 in sub-Saharan populations due to frequent coinfections. Our previous research showed that unsuppressed HIV is associated with weaker immune responses to SARS-CoV-2, but the underlying mechanisms are unclear. We investigated how pre-existing T cell immunity against an endemic human coronavirus HCoV-NL63 impacts SARS-CoV-2 T cell responses in people living with HIV (PLWH) compared to uninfected individuals, and how HIV-related T cell dysfunction influences responses to SARS-CoV-2 variants.We used flow cytometry to measure T cell responses following PBMC stimulation with peptide pools representing beta, delta, wild-type, and HCoV-NL63 spike proteins. Luminex bead assay was used to measure circulating plasma chemokine and cytokine levels. ELISA and MSD V-PLEX COVID-19 Serology and ACE2 Neutralization assays were used to measure humoral responses. This is a provisional file, not the final typeset article Results: Regardless of HIV status, we found a strong positive correlation between responses to HCoV-NL63 and SARS-CoV-2. However, PLWH exhibited weaker CD4⁺ T cell responses to both HCoV-NL63 and SARS-CoV-2 than HIV-uninfected individuals. PLWH also had higher proportions of functionally exhausted (PD-1high) CD4⁺ T cells producing fewer proinflammatory cytokines (IFNγ and TNFα) and had elevated plasma IL-2 and IL-12(p70) levels compared to HIV-uninfected individuals. HIV status didn't significantly affect IgG antibody levels against SARS-CoV-2 antigens or ACE2 binding inhibition activity.Our results indicate that the decrease in SARS-CoV-2 specific T cell responses in PLWH may be attributable to reduced frequencies of pre-existing cross-reactive responses. However, HIV infection minimally affected the quality and magnitude of humoral responses, and this could explain why the risk of severe COVID-19 in PLWH is highly heterogeneous.